Will Curtains Come Down for the Sustainable Theatre – Evaluating Growth Challenges from an Island Nation - Tan, Seck (European Journal of Sustainable Development, 2019)
Sustainable development (as defined by The Brundtland Report, 1987) points to development that meets the needs of the present without compromising the ability of future generations to meet their own. However, sustainable development denotes different perspectives to different audience; and for development to be truly sustainable, growth must be inclusive and demands equal attention to the tri-nexus of economy, society and the environment. Unfortunately, this is far from reality. In an effort to continue growing, economies pedestalize economic progress where attention is skewed towards economic performance with an intentional disregard of the environment and to the degradation of the environment. For the purpose of this paper, sustainable development focuses on debates between the twin-nexus of economy and the environment. This paper highlights sustainable development challenges for Singapore (an island nation). While most studies centered on Singapore?s miraculous growth, few have examined the island?s use of its environmental capital for economic growth. Island economies face similar development challenges like most global economies; the difference lies in their natural endowments (or the lack of). This underlines the need for policies to advance ecosystem preservation in land-scarce Singapore. With the use of a simple environmental valuation framework, it is demonstrated that the island nation has not fared too badly in protecting its environmental capital. Keywords: Ecosystem, Environmental Capital, Island Nation, Singapore, Sustainable Development